The Rhetoric of "Board of Peace" Diplomacy: an Analysis of Prabowo Subianto's Political Communication in Balancing Palestinian Support and Israeli Security Guarantees: Penelitian - Syamsul Efendi; Rabith Madah Khulaili Harsya; Bambang Amir Al-Hakim; Muhammad Thalal; Abd Razak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study analyzes the political communication rhetoric of Indonesia's defense diplomacy under Prabowo Subianto, specifically focusing on the conceptualization of the "Board of Peace" framework. Indonesia has traditionally maintained a staunch, constitutionally mandated pro-Palestinian stance while avoiding formal diplomatic ties with Israel. However, contemporary geopolitical shifts require a more nuanced, pragmatic communication strategy that balances ideological solidarity with international security realism. Utilizing a qualitative approach rooted in rhetorical analysis and political discourse frameworks, this paper examines Prabowo's public speeches, international forum addresses, and diplomatic statements regarding the Middle East conflict. The analysis reveals that the "Board of Peace" rhetoric functions as a dual-targeted communication instrument. On one hand, it employs an ethos of Islamic and anti-colonial solidarity to satisfy domestic constituencies and regional allies. On the other hand, it utilizes a pragmatic logos that acknowledges the structural realities of Israeli security guarantees as a prerequisite for any viable two-state consensus. Indonesia is shifting to defensive realism: from being a passive supporter of Palestine to an active global mediator.